Pengaruh Kesadaran Wajib Pajak dan Moral Wajib Pajak Terhadap Kepatuhan Wajib Pajak UMKM di Kota Bekasi - Nursifah Marwah; Daryanto Hesti Wibowo (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
The contribution of MSMEs to the National Gross Domestic Product (GDP) according to current prices in 2018 is around 60% or 60 million, but only 1.5 million pay taxes or 2.2% of income tax receipts. Then, as of April 1, 2019 the Directorate General of Taxes recorded the realization of annual notification letter reporting (SPT) of 11.309 million people, or the equivalent of 61.7% of 18.334 million taxpayers. This shows that there is still low awareness and compliance with taxation by taxpayers. This research wants to make an academic contribution to the picture of optimizing the tax potential of Micro, Small, and Medium Enterprises (MSMEs) through the Awareness and Moralty approach. The type of research used id explanatory with a quantitative approach. The research was conducted on a sample of Small and Medium Enterprises (SMEs) in Bekasi City (West Bekasi). The hypotheses tested are 1) The significant effect of Taxpayer Awareness on Tax payer Compliance of Micro, Small, and Medium Enterprises (MSMEs); 2) The significant influence of Taxpayer Morale on Taxpayer Compliance; 3) Simultaneously and significantly the effect of Taxpayer Compliance of Micro, Small, and Medium Enterprises (MSMEs).